SCOPE FOR SUPER-SPECIALIZATION IN FORENSIC MEDICINE & TOXICOLOGY: WAY FORWARD (Journal of Forensic Medicine & Toxicology, 2024)
Science keeps on advancing day by day and one of its excellent examples is Medical Science, where, once the field of General Medicine/ General Surgery was sufficient to deal with all diseases and pathological conditions of the body, but now we all know that with the development of super-specialization in many fields, the horizon of Forensic Medicine,Superspecialization,Toxicology. Forensic Medicine is defined as the application of knowledge of medicine and allied subjects to law for the administration of justice. Medical Jurisprudence is the application of various aspects of law to the day to day practice of Medicine
Keywords: uplift; pathological; SUPER-SPECIALIZATION